The Yajña Chakra in Sujana human education - Yuliani, Ni Made; Rahayu , Ni Wayan Sri (Institute for Advanced Science Social, and Sustainable Future, 2024)
Education in Indonesia is always in the public spotlight, usually during the period of cabinet changes. Particularly, the Minister of National Education, who is always concerned with new policies along with new curriculum, which has an effect on parents and students as well as the wider community. Indonesia's human development index in 2022 reached 72.91, an increase of 0.62 points (0.86 percent) compared to the previous year (72.29). In terms of determining the development index, education is one of the keys. In this article, qualitative research examines the Yajña Chakra Concept in Sujana Human Education efforts. The data in this research was obtained through observation, literature study, interviews and Focus Group Discussions (FGD) related to the research theme and studied using content analysis. According to the Vedas, the philosophical background of education is to improve the quality of life of